Inside Back Cover: A Major Advance in the Synthesis of Fluoroalkyl Pyrazoles: Tuneable Regioselectivity and Broad Substitution Patterns (Chem. Eur. J. 32/2016). Issue 32 (20th June 2016) - Schmitt, Etienne; Panossian, Armen; Vors, Jean‐Pierre; Funke, Christian; Lui, Norbert; Pazenok, Sergiy; Leroux, Frédéric R.
Abstract : Fluoroalkyl pyrazoles, which are key building blocks in agrochemistry and promising candidates in life‐science‐oriented research, have shown much potential in accessing a variety of bis(fluoroalkyl)pyrazoles with tunable regioselectivity of the hydrazine addition, via two intermediates of opposed reactivity. The two strategies are represented by one slingshot aiming at two different targets, with a background of crops, forests, and laboratory activities. More information can be found in the Full Paper by S. Pazenok, F. R. Leroux et al. on page11239 .